Dose-Responsive Mitigation of Hepatic Oxidative Stress and Histopathological Damage by Channa striata Extract in Post-Carbon Tetrachloride-Exposed Rats - OK Yulizal; Susan Gabriella Br Sinulingga; Yolanda Eliza Putri Lubis (Jurnal Penelitian Pendidikan IPA, 2026)
Carbon tetrachloride (CCl₄) is widely used to induce experimental oxidative liver injury through the generation of free radicals that promote lipid peroxidation and hepatocellular damage. Natural products with antioxidant properties are being explored for their potential to mitigate such injury. This study aimed to evaluate the dose-responsive ameliorative effects of Channa striata extract on hepatic oxidative stress and histopathological alterations in rats following subacute CCl₄ exposure. Thirty male Wistar rats were divided into five groups: normal control (K1), CCl₄ control (K2), and three treatment groups receiving C. striata extract at 100, 150, and 200 mg/kg body weight/day for two weeks after six weeks of CCl₄ induction (K3–K5). Hepatic malondialdehyde (MDA) levels were measured as an indicator of lipid peroxidation. Liver histopathology was assessed for hepatocellular necrosis, congestion, and inflammatory cell infiltration using a semi-quantitative scoring system. CCl₄ exposure significantly increased hepatic MDA levels and caused severe histopathological damage in the control group. C. striata extract dose-dependently attenuated MDA levels (p < 0.001), with the 200 mg/kg/day group showing the lowest levels (2.80 ± 0.15 vs. 6.65 ± 0.13 nmol/g in CCl₄ control). Histopathological scores for necrosis, congestion, and inflammatory infiltration ameliorated progressively with increasing doses, with median total scores improving from 8.5 (CCl₄ control) to 2.0 (200 mg/kg/day). Channa striata extract demonstrates dose-dependent ameliorative activity against established CCl₄-induced oxidative liver injury, as evidenced by attenuation of lipid peroxidation and mitigation of histopathological damage. Further studies incorporating serum liver enzymes and molecular mechanisms are warranted.